Stretchable electrochemical energy storage devices. (2nd June 2020) - Mackanic, David G.; Chang, Ting-Hsiang; Huang, Zhuojun; Cui, Yi; Bao, Zhenan
Abstract : Deformable energy storage devices are needed to power the next generation of wearable electronics. This review highlights the most recent advances in stretchable energy storage devices with a focus on batteries and supercapacitors. Abstract : The increasingly intimate contact between electronics and the human body necessitates the development of stretchable energy storage devices that can conform and adapt to the skin. As such, the development of stretchable batteries and supercapacitors has received significant attention in recent years. This review provides an overview of the general operating principles of batteries and supercapacitors and the requirements to make these devices stretchable. The following sections provide an in-depth analysis of different strategies to convert the conventionally rigid electrochemical energy storage materials into stretchable form factors. Namely, the strategies of strain engineering, rigid island geometry, fiber-like geometry, and intrinsic stretchability are discussed. A wide range of materials are covered for each strategy, including polymers, metals, and ceramics. By comparing the achieved electrochemical performance and strain capability of these different materials strategies, we allow for a side-by-side comparison of the most promising strategies for enabling stretchable electrochemical energy storage. The final section consists of an outlook for future developments and challenges for stretchable supercapacitors and batteries.